2011
DOI: 10.1021/ol200194y
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed α-Arylation of Nitriles and Esters and γ-Arylation of Unsaturated Nitriles with TMPZnCl·LiCl

Abstract: Using TMPZnCl·LiCl as a kinetically highly active base, nitriles and esters undergo a Pd-catalyzed α-arylation under mild conditions. Remarkably, in the case of α,β- or β,γ-unsaturated nitriles, a regioselective γ-arylation or a γ-alkenylation is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 55 publications
0
24
0
8
Order By: Relevance
“…[12,13] Besides, 7 proved to be an excellent base for the generation of nitrile and ester enolates. [13,14] We have also demonstrated that 7 is compatible with additional strong Lewis acids (MgCl 2 , BF 3 ·OEt 2 ) and forms frustrated Lewis pairs.…”
mentioning
confidence: 66%
“…[12,13] Besides, 7 proved to be an excellent base for the generation of nitrile and ester enolates. [13,14] We have also demonstrated that 7 is compatible with additional strong Lewis acids (MgCl 2 , BF 3 ·OEt 2 ) and forms frustrated Lewis pairs.…”
mentioning
confidence: 66%
“…The residual bromide in 30 allowed for the rapid attachment of the entire ester side chain by a palladium‐catalyzed enolate arylation reaction. After some experimentation, it was found that this transformation was best achieved by deprotonation of acetate 31 with TMPZnCl⋅LiCl, followed by palladium‐catalyzed cross‐coupling of the resulting enolate 51. Gratifyingly, the resulting diyne derivative 32 could be cyclized in good yield by RCAM, although the somewhat less encumbered complex 6 (Scheme ), activated in situ on treatment with CH 2 Cl 2 as previously described by our group,52 had to be used for optimal results 53.…”
Section: Resultsmentioning
confidence: 99%
“…39 Most recently, Knochel reported three examples of palladium-catalyzed α-arylation reactions of zinc ester enolates. 40 These zinc enolates are formed by reaction of ethyl butyrate or isobutyrate with (TMP)ZnCl•LiCl. Because palladium-catalyzed α-arylation of alkali metal enolates occurred in high yields in the presence of catalyst systems bearing sterically hindered, electron-rich alkylphosphines, 24,26-28,31 we sought to develop general procedures for the palladium-catalyzed α-arylation of Reformatsky reagents.…”
Section: Introductionmentioning
confidence: 99%